The HUSH Project: Using codesign to reduce sleep disruptions for patients in hospital - Corey Adams; Ramesh Walpola; Anthony Schembri; Reema Harrison (Health Expectations, 2024)
Abstract Background Poor quality sleep in hospitals may be problematic for patients, negatively impacting their recovery and wellbeing. This project aimed to investigate the effectiveness of codesign in addressing key issues affecting sleep disruption in the healthcare setting. Methods Codesign with patients, staff and consumer representatives was conducted in an acute metropolitan tertiary public hospital in Sydney, Australia. Through a four‐stage process, a multimodal intervention to address and reduce the impact of sleep disruptions among hospital inpatients was created. Pre‐ and post‐intervention evaluation was used to determine changes in patient‐reported sleep disruption. Results ‘The HUSH Project’ (Help Us Support Healing) intervention resulted from the codesign process, which included the provision of HUSH Sleep Packs (with earplugs, eye masks and herbal tea), patient information resources, and ward‐based Sleep Champions. Survey data from 210 patients revealed a statistically significant decrease in patient‐reported noise disturbances for patients in shared rooms following the 4‐week intervention period of the HUSH program. Conclusion The HUSH Project demonstrated that a novel multimodal intervention may be valuable in reducing sleep disruption in hospitals. These findings also indicate the benefits of using codesign methodology to support improvement projects that seek to enhance patient experiences of care. Patient or Public Contribution This project utilised codesign methodology, which involved significant contributions from patients and consumer representatives, from research conceptualisation into intervention design, implementation and project evaluation.